MALARIA CENTER: SEBUAH MODEL PENGUATAN SISTEM PENGENDALIAN PENYAKIT MALARIA DI PROVINSI MALUKU UTARA - Yuningsih, Rahmi (Jurnal Aspirasi, 2011)
North Moluccas is a malaria endemic area. The clinical prevalence decline from 81,3‰ in 2003 to into 38‰ in 2010. Such a sharp decline is considered as a great success of the Malaria Center development initiative that has been in operation since 2003. The purpose of this research is to know how the Malaria Center is developed in North Moluccas. The research was conducted using the Focus Group Discussion approach that was implemented involving the stakeholders in early April 2011. The result shows that the Malaria Center development initiative is indeed the key for the success in reducing the malaria prevalence in 2003-2009. Its strength point is the strategy in advocacy, partnership and empowerment that are catalytically created a malaria control system with a complete and sufficient size of elements include human resource, budget, logistic, laboratory as well as recording and reporting. This initiative may be replicated, perhaps with some adaptations, in other malaria endemic areas.